POTENTIALLY ENHANCEMENT OF POSTPARTUM PSYCHOLOGICAL DISORDERS IN THE PANDEMIC OF COVID-19 - Ineke Permatasari (Journal of Psychiatry Psychology and Behavioral Research, 2023)
Background: The resulting consequences of pandemic COVID-19 include non-natural disasters, as well as trauma, which causes challenges in the psychological field due to the resulting situational under pressures. This can also be used as a benchmark for psychological well-being in postpartum women. The process of giving birth is one of the stressful events for the mother and this is a critical period for the mother, it can cause some physical and psychological damage due to unpleasant experiences during childbirth, such as difficult cases, prolonged labor, and traumatic manipulation during labor.Objective: To discussed the factors that can have a potential effect on the risk of this incident, the potential to exacerbate psychological disorders in postpartum women, including factors from a medical, social, and psychological perspective.Method: This paper involved on referral sources and based on observation by author.Results: Prevalence of disorders such as depression and PTSD increased during the COVID-19 pandemic. Other supportive conditions such as the lack of mental support from families, the process of independent isolation, limited access to health services which also causes stress and feelings of being alone. Based on the literature, all of these events can create fear and suppress the mental state of the post partum woman, hinder the postpartum process of transition, and increase the intensity of depression severityConclusion: Pandemic COVID-19 made alleviate of postpartum psychological disorder, therefore preventive effort can be choosen to bring positive impact by increasing productivity and make a positive mind in the mother, also described as an efficient and useful method for postpartum mothers. Keywords: enhancement, psychological, pregnancy.